In vitro investigation of canine periodontal ligament-derived mesenchymal stem cells: A possibility of promising tool for periodontal regeneration - Hamideh Salari Sedigh; Anna Saffarpour; Shahram Jamshidi; Mahdi Ashouri; Seyed Mahdi Nassiri; Mohammad Mehdi Dehghan; Esmail Ranjbar; Reyhaneh Shafieian (Elsevier, 2023)
Objectives: Recent investigations indicate that canine periodontal ligament-derived stem cells (cPDLSCs) may reveal a reliable strategy for repair of periodontal tissues via cell-based tissue engineering approaches. Due to limited research, this study aimed to demonstrate the phenotypic characterization of cPDLSc in comparison with canine bone marrow-derived mesenchymal stem cells (cBMSCs) in vitro. Methods: Mesenchymal stem cells (MSCs) were obtained from PDL and BM of five male adult Mongrel dogs. In vitro isolation and expansion as well as biologic characterization including colony unit formation (CFU), osteogenic and adipogenic differentiation, flow cytometric analysis of CD34 and CD44, and RT-PCR of alkaline phosphatase (ALP), osteocalcin (OCN), periostin (POSTN) and S100A4 were performed. Furthermore, electron microscopy analysis was done to complement the comparative research. Results: CFU assay revealed that colonies of cPDLSCs presented 70% confluency with a more finite lifespan than BM-MSCs, showing a significant increase in cPDLSCs. Both types of MSCs showed osteogenic and adipogenic phenotypic characterized with clusters of mineralized depositions and lipid vacuoles, respectively. Both types of MSCs expressed CD44 with limited expression of CD34. RT-PCR of cPDLSCs revealed that expression of ALP, POSTN, OCN and S100A4 genes were significantly higher than those of BMSCs. In addition, comparison of SEM and revealed that cPDLSCs expressed more extracellular collagen fibers. Conclusions: The current study indicated that cPDLSCs show potency as a novel cellular therapy for periodontal regeneration a large animal model.